2010
DOI: 10.1016/j.biopsych.2009.12.020
|View full text |Cite
|
Sign up to set email alerts
|

Flexible Accelerated STOP Tetracycline Operator-Knockin (FAST): A Versatile and Efficient New Gene Modulating System

Abstract: We created the FAST (Flexible Accelerated STOP TetO-knockin) system, an efficient method for manipulating gene expression in vivo to rapidly screen animal models of disease. A single gene targeting event yields 2 distinct knockin mice -STOP-tetO and tetO knockin-which permit generation of multiple strains with variable expression patterns: 1) knockout, 2) Cre-mediated rescue; 3) tTA-mediated misexpression; 4) tTA-mediated overexpression; and 5) tTS-mediated conditional knockout/knockdown. Using the FAST system… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
123
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
10

Relationship

5
5

Authors

Journals

citations
Cited by 103 publications
(125 citation statements)
references
References 15 publications
2
123
0
Order By: Relevance
“…Since noncanonical Wnt proteins were increased in the EAE spinal neurons (Fig. 1), transgenic Wnt5a expression in the TetO-Wnt5a mice was driven by mating them with CaMK2-tTA mice (20), in which tTA expression was specifically induced in CNS excitatory neurons and cerebellar Purkinje cells and granule cells (CaMK2-tTA; TetO-Wnt5a mice) (20,45). Previously, it has been reported that spinal neurons express both CaMK2␣ and CaMK2␤ in the ventral gray matter of the spinal cord (46).…”
Section: Resultsmentioning
confidence: 99%
“…Since noncanonical Wnt proteins were increased in the EAE spinal neurons (Fig. 1), transgenic Wnt5a expression in the TetO-Wnt5a mice was driven by mating them with CaMK2-tTA mice (20), in which tTA expression was specifically induced in CNS excitatory neurons and cerebellar Purkinje cells and granule cells (CaMK2-tTA; TetO-Wnt5a mice) (20,45). Previously, it has been reported that spinal neurons express both CaMK2␣ and CaMK2␤ in the ventral gray matter of the spinal cord (46).…”
Section: Resultsmentioning
confidence: 99%
“…We developed an inducible GARP OE mouse model using the "Flexible Accelerated STOP TetO knockin system" (Ingenious Targeting Laboratory) (86). Development of the GARP-FAST mouse model has been described previously (45).…”
Section: Methodsmentioning
confidence: 99%
“…90 Moreover, "reversible" knockout models make it possible to study time-and region-specific consequences of developmental interruptions in receptors. 163 For instance, it has recently been shown that knockout of the 5-HT 1A autoreceptor in 5-HT raphe neur ons 14-30 days after birth (corresponding to early childhood) leads to long-lasting increases in anxiety, decreased social behaviours and subtle alterations in neuron physiology. 164 In humans, improvements in compounds that permit the visualization of 5-HT target molecules in the human brain have helped us to understand the expression of receptors or proteins in the human brain.…”
Section: The 5-ht Hypothesis Of Psychopathology: What Has It Taught Umentioning
confidence: 99%